Activation Policies in Ireland - Grubb, David (OECD Publishing, 2009)
In Ireland the placement function of the Public Employment Service (PES) is primarily within FÁS, the Training and Employment Authority, which is supervised by the Department of Enterprise, Trade and Employment (DETE). But employment counselling services are also provided by the "Local Employment Service" (which has partly-separate funding and management arrangements); Facilitators within the Department of Social and Family Affairs (who implement an "Activation Programme", which however lacks participation requirements); and the "Services to the Unemployed" activity within the Local Development Social Inclusion Programme (which is managed through a third Department). The number of staff in FÁS Employment Services and the Local Employment Service, relative to the number of wage and salary earners in the economy, appears to be relatively low, about half the average level of staffing of institutions responsible for the placement function in Australia and Northern and Western Europe (countries which also have high benefit coverage rates for unemployment)
Keywords: Social Issues/Migration/Health; Ireland